Monkeypox Disease with Predominant Genital Symptoms: A Nigerian Case Report - , Golden Owhonda; , Ihuoma Aaron Wali; , Ifeoma Nwadiuto; , Victor Abikor; , Livingstone Solomon; , Anwuri Luke; , Hastings Onu; , Victor Onyiri; , Ndubuisi Akpuh (Archives of Current Research International, 2023)
Mpox presents typically with macular papular body rashes with similar-looking sores in genital or oral areas. It may be missed, or wrongly managed as sexually transmitted infections (STI), especially in settings where symptom-based treatment practices are sufficient for care. We describe a 40-year-old cisgender male, heterosexual Nigerian who developed some rash in the genital region associated with penile swelling. It was suspected to be syphilis and managed with presumptive antibiotics. Laboratory investigation (PCR) confirmed that it was a Mpox disease, and VDRLT was negative. Notably, in this case, the early symptoms were a paradigm case of Mpox disease presenting as an STI, which syndromically conformed more to an STI than the case definition for a suspected case of Mpox in our setting. Consequently, the expected early containment activities were delayed. This increased the potential of further disease spread. An Update of the standard case definition as well as a reclassification of the disease as a possible STI is recommended for enhanced surveillance, increased case detection, and reduction in the burden of unrecognized cases.